A Preliminary Survey of Domiciliary Cockroaches and Their Oothecal Parasites in Sri Lanka - Kumarasinghe, N.C.; Edirisinghe, Jayanthi P. (My University, 1991)
A survey of domiciliary cockroaches and their oothecal parasites was carried out in 17 districts. The study was based on empty and live cockroach oothecae collected from dwelling houses. Five species of cockroaches; Periplaneta americana (L.) Neostylopyga rhombifolia (Stoll) Periplaneta australasiae (F.) Supella longfpalpa (F.) and Blatella germanica (L.) were found frequenting houses. Of them, P. american a was the most abundant and widely distributed species, while B. germanlca was the least abundant species. P. americana and N. rhombifolia were present in all but one district, while P. australaslae and S. longipalpa were confined to 12 and 08 districts respectively. Mannar district was peculiar in that only one domiciliary species, N. rhombifolia was recorded from there. Only two species of oothecal parasites, Tetrastlchus hagenowli (Ratz.) and Evania appendlgaster (L.) were encountered during the study. Each of these parasite species was characterized by the size of the emergence hole they made in cockroach oothecae. Thus on the basis of the emergence hole alone it was possible to categorize the empty oothecae as being parasitized. Of the oothecae, those of P. americana and P. australiasae were parasitized by both species of parasites, while oothecae of N. rhombifolla was parasitized by T. hagenowii only. Oothecae of S. longipalpa and B. germanica were not parasitiized at all. There appears to be a great paucity in the oothecal parasite fauna of Sri Lanka, compared to India where eight species of hymenopterans are known to parasitize oothecae of domiciliary cockroaches. The possibility of controlling household cockroaches using local and introduced parasites remains to be explored. The shortcomings in this preliminary survey are also reported.
Keywords: Domiciliary cockroaches; Oothecal paracites